2002
DOI: 10.1111/j.1945-5100.2002.tb01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined noble gas and trace element measurements on individual stratospheric interplanetary dust particles

Abstract: Abstract-The trace element compositions and noble gas contents of 32 individual interplanetary dust particles (IDPs) collected in the Earth's stratosphere were measured. Trace element compositions are generally similar to CI meteorites, with occasional depletions in ZnRe with respect to CI. Noble gases were detected in all but one of the IDPs. Noble gas elemental compositions are consistent with the presence of fractionated solar wind. A rough correlation between surface-normalized He abundances and ZnIFe rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 29 publications
(16 reference statements)
4
47
0
Order By: Relevance
“…As discussed below, the solar noble gases indicate that the SEC grains came to Earth as small particles. The element ratios 4 He/ 22 Ne lie between the atmospheric (3.1) and the solar (~9000) value, indicating partial loss of solar gases, as is also observed for recent interplanetary dust particles (IDPs) (Kehm et al 2002).…”
Section: Sediment-dispersed Extraterrestrial Chromite Grainssupporting
confidence: 56%
“…As discussed below, the solar noble gases indicate that the SEC grains came to Earth as small particles. The element ratios 4 He/ 22 Ne lie between the atmospheric (3.1) and the solar (~9000) value, indicating partial loss of solar gases, as is also observed for recent interplanetary dust particles (IDPs) (Kehm et al 2002).…”
Section: Sediment-dispersed Extraterrestrial Chromite Grainssupporting
confidence: 56%
“…Detailed studies of individual cosmic dust particles began with the recovery of magnetic cosmic spherules from the ocean floor (Bradley and Brownlee 1982) and later of interplanetary dust particles (IDPs) by high-altitude aircraft (Brownlee 1985). Schlutter (1990, 1993), Kehm et al (1998Kehm et al ( , 2002Kehm et al ( , 2006, and Pepin et al (1999Pepin et al ( , 2000Pepin et al ( , 2001) have all reported on cosmogenic and solar gases in IDPs.…”
Section: Introductionmentioning
confidence: 99%
“…Errors are 1σ . (Nier andSchlutter, 1990, 1993;Kehm et al, 2002) and ice-AMMs (Osawa and Nagao, 2002;Osawa et al, 2003a) are presented for comparison. The ratios for solar abundance (850: Anders and Grevesse, 1989) and SW (556: Heber et al, 2009) Ar ratio slightly higher than those of both SW and Q would be fractionated SW-Ar as in case of He and Ne in the snow-AMMs, although trapped Fig.…”
Section: Light Noble Gases He and Ne In The Snow-ammsmentioning
confidence: 99%
“…and reported He and Ne isotopic ratios attributed to implantation of solar energetic particles ("SEP") in individual IDPs and spherules from deep sea sediments, although this composition has now been shown to be implantation of mass discriminated solar wind "SW" (Grimberg et al, 2008). Laser heating methods have been used to extract noble gases from single IDPs; the measured He, Ne, and Ar were of solar origin (Kehm et al, 1998(Kehm et al, , 2002. Isotopic compositions of all noble gases for more than 100 individual iceAMMs have been measured using a Nd-YAG laser combined with a low blank and highly sensitive mass spectrometer (e.g.…”
Section: Introductionmentioning
confidence: 99%